2012
DOI: 10.22358/jafs/66072/2012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for lactose percentage in the milk of Polish Holstein-Friesians

Abstract: Genetic parameters for lactose percentage in the milk of Polish Holstein-Friesian cows were estimated using 48,859 test day records from six lactations of 8,418 cows and the Gibbs sampling method. The multiple-trait random regression model was applied for data from the first and subsequent (up to the sixth) lactations treated as two traits. Variance components and heritabilities changed in a similar way through the first and subsequent lactations, reaching the highest values at peripheries and relatively stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
(48 reference statements)
3
12
3
Order By: Relevance
“…This disagrees with reports by Miglior et al (2006) and Ptak et al (2012), who found that the lactose curve was very similar to the milk yield curve, with a maximum value between 30 and 60 days and a gradual decrease in the remaining days. Miglior et al (2006) found that the lowest lactose concentration occurred in summer time.…”
Section: Discussioncontrasting
confidence: 99%
“…This disagrees with reports by Miglior et al (2006) and Ptak et al (2012), who found that the lactose curve was very similar to the milk yield curve, with a maximum value between 30 and 60 days and a gradual decrease in the remaining days. Miglior et al (2006) found that the lowest lactose concentration occurred in summer time.…”
Section: Discussioncontrasting
confidence: 99%
“…The heritabilities for SCS were lower than the heritabilities for the production traits, and were equal to 0.13, 0.14 and 0.16 for the first three parities, respectively. The heritabilities for production traits and SCS were within the ranges reported for Polish Holstein-Friesians (Strabel et al 2004 ; Strabel and Jamrozik 2006 ; Yazgan et al 2010 ; Jesiołkiewicz et al 2011 ; Rzewuska et al 2011 ; Ptak et al 2012 ) and all—except the heritability for SCS—were lower than those obtained for Canadian and Dutch populations (Wood et al 2003 ; Miglior et al 2007 ; Stoop et al 2007 ). A similar relation between heritabilities estimated for the production traits of the Polish and Canadian populations, with higher values for the latter, was indicated in an earlier study (Strabel et al 2004 ).…”
Section: Resultssupporting
confidence: 61%
“…However, the lactose content found by Brito et al (2011) was much lower (0.17) than that presented in our and Andonov et al (2007) studies. In the literature different results for lactose content in cow's milk are presented -from 0.17 to 0.36, depending of the stage of lactation and parity with the lowest at the beginning of the first lactation (Ptak et al, 2012) up to an average heritability of 0.48 in the first, and 0.51 in the second and later parities (Miglior et al, 2007).…”
Section: Resultsmentioning
confidence: 99%